Transport for under two degrees – the way forward. 10 key insights for the decarbonisation of the transport sector. A global foresight study. - Hochfeld, Christian; Pützschler, Marena; Wanko, Matthias; Jung, Alexander; Enskat, Mike; Mettke, Christian; Major, Mark; Sohm, Stefanie; Wolff, Christoph (My University, 2020)
To identify the necessary action for a full decarbonisation of transport, the study applied methods of strategic foresight: In particular, these methods comprised context mapping in the form of a systematic literature review on international transport scenarios and 56 qualitative interviews with international senior experts primarily from the transport and energy sectors. Subsequently, a two-stage Delphi survey was conducted. A Delphi survey is a structured, iterative group facilitation technique that has been developed as a systematic, interactive forecasting method. 290 international experts participated in the first round of the survey; 103 experts took part in round two. The project was implemented between March 2018 and February 2020.
Keywords: Verkehrssektor; Dekarbonisierung; Verkehrsemission; Emissionsminderung; Umweltziel; Klimaschutzprogramm; Nachhaltige Verkehrsentwicklung; Literaturauswertung; Expertenbefragung; Forschungsprojekt